National Patterns of Filled Prescriptions and Third-Line Treatment Utilization for Privately Insured Women With Overactive Bladder. Issue 2 (February 2021) - Linder, Brian J.; Gebhart, John B.; Elliott, Daniel S.; Van Houten, Holly K.; Sangaralingham, Lindsey R.; Habermann, Elizabeth B.
Abstract : Objective: The aim of this study was to evaluate national patterns of care for women with overactive bladder (OAB) in an administrative data set and identify potential areas for improvement. Methods: We performed an analysis using the OptumLabs Data Warehouse, which contains deidentified administrative claims data from a large national US health insurance plan. The study included women, older than 18 years, with a new OAB diagnosis from January 1, 2007, to June 30, 2017. We excluded those with an underlying neurologic etiology, with interstitial cystitis/painful bladder syndrome, were pregnant, or did not have continuous enrollment for 12 months before and after OAB diagnosis. Trends in management were assessed via the Cochran-Armitage test. Time to discontinuation among medications was compared using t test. Results: Of 1.4 million women in the database during the study time frame, 60, 246 (4%) were included in the study. Median age was 61 years [interquartile range (IQR), 50–73], and median follow-up was 2.6 years (IQR, 1.6–4.2). Overall, 37% were treated with anticholinergics, 5% with beta-3 agonists, 7% with topical estrogen, and 2% with pelvic floor physical therapy; 26% saw a specialist; and 2% underwent third-line therapy. Median time to cessation of prescription filling was longer for beta-3 agonists versus anticholinergics [median, 4.1 months (IQR, 1–15) vs 3.6 months (IQR, 1–10); P < 0.0001]. Use of third-line therapies significantly increased over the study time frame, from 1.1% to 2.2% ( P < 0.0001). Conclusions: Most of the patients do not continue filling prescriptions for OAB medications, and a minority of patients were referred for specialty evaluation. Although third-line therapy use is increasing, it is used in a small proportion of women with OAB. Given these patterns, there may be underutilization of specialist referral and other OAB therapies. Abstract : Supplemental digital content is available in the text.